Investigating the Impact of Academic Procrastination on EFL Learners’ Achievements - GOUASMIA, Abdellah (My University, 2020)
Procrastination is a widespread phenomenon in the academic context. It is the act of postponing tasks and delaying them to an indefinite time and date. This psychological phenomenon makes learners unable to undertake the tasks they are requested to do in a definite time; this is due to many factors. The latter can affect and manipulate learners’ procrastination. In this dissertation, this study aims to investigate the negative impact of academic procrastination on EFL Learners’ academic life. The data collection instruments used for this research were an interview and a questionnaire to collect relevant information we need for the topic. We selected 30 third-year licence students of English and 10 EFL teachers from AbdelhamidIbnBadis University in Mostaganem. The results revealed that our participants confirm that academic procrastination kept learners from progressing in their educational carrier and affected their skills by reducing their autonomy and engagement inside and outside the classroom. Procrastination is a deeply ingrained psychological problem that learners should avoid and that teachers should be aware of its negativity. Finally, academic procrastination, from the perspectives of our participants, is as a harmful habit that sticks to affect their learning process, causing total degradation, low assessment and a gap between them and their teachers.
A case of Third year students of English, Mostaganem
Keywords: Procrastination; Academic procrastination; Achievements